New substituted imidazo[1, 5-a]pyridine and imidazo[5, 1-a]isoquinoline derivatives and their application in fluorescence cell imaging. (October 2018) - Volpi, G.; Lace, B.; Garino, C.; Priola, E.; Artuso, E.; Cerreia Vioglio, P.; Barolo, C.; Fin, A.; Genre, A.; Prandi, C.
Abstract: A series of new dyes based on the fluorescent imidazo[1, 5- a ]pyridine moiety has been designed and synthesized specifically for fluorescence cell imaging application. The obtained molecules contain a carboxylic functional group inserted to increase the water solubility and to provide an effective conjugation site. Their structural and optical properties have been deeply investigated and compared with theoretical calculations. The suitability of the products as fluorescent labels for cell imaging applications has been investigated by laser scanning confocal microscopy, both in vivo on Arabidopsis thaliana seedlings and in vitro, on mouse fibroblast cells. The compounds displayed good permeability to the plant cell wall and plasma membrane, they were efficiently internalized in the inner plant tissues, and retained a strong fluorescence in aqueous media.